Giving Instruction in the English Language Classroom: Principles and the Practices - Poudel, Guru Prasad (Shiksha Shastra Saurabh, 2025)
Teaching English is often perceived as a challenging task to the teachers. One of the reasons behind the challenge is teachers’ difficulties to get students attentive in learning and help them understand the meaning. Not only the case of teachers, many of the learners find learning English as a headache. Sowell (2017) admits that one of the probable headaches in learning English is not being able to receive proper instruction. Sometimes students receive very little instruction whilst sometimes they receive no instruction at all. In my experience too, most of us just ask students do language tasks, such as listen and complete, read and write summary, give a short description, etc. without providing clear cut instruction on what to do, how and why. Teachers’ instruction in the classroom works as the guidance for task completion. And the absence of proper instruction in teaching English creates difficulties to perform required tasks and misleads the students, as a result, students show very little interest to do what they are asked to do or even leave the task incomplete. Considering such a situation, this article aims at introducing the instruction in teaching, discussing the importance, presenting the principles, suggesting processes and sharing hands-on tips for instruction giving in ELT classes. It has been developed from the review of related literature and self-reflection. The entire discussion enabled me to conclude that instruction giving is always desirable in teaching English if we wish to get students complete the tasks and have meaningful learning.